Designing Chemistry Learning Media to Train Ecopreneurship - Rusly Hidayah; Achmad Lutfi; Dian Novita (Newinera Publisher, 2021)
The purpose of this research is to get the draft chemistry learning media design developed to support ecopreneurship. Ecopreneurship at FMIPA UNESA is broken down into eco-innovation (new ideas), eco opportunities, and eco commitment. Design of this research is giving the assignment to research objectives. The model development research with stages, SMK learning in class, students doing assignments, arrange learning media design, assessing game design, and data analysis. The assignment is compiling a plan for developing instructional media that can be applied in chemistry learning in SMK. That assignment was assessed by 3 experts and the score was averaged. The assessment has been fulfilled if all media plans have met the fulfillment criteria. The innovation of chemistry media was also assessed and has met the innovation when obtaining an average of at least 4 with a maximum scale of 5. This research was conducted at the Department of Chemistry FMIPA UNESA in the odd semester of the academic year 2019/2020. the results showed 4 vocational chemistry learning media designs, (1) VCO-Making KIT, (2) Voltaic Cell KIT, (3) Acid-base Mini Lab, and (4) Red and Ox Games. All of that has fulfilled the contents and construct besides that the student has a new idea.